An Investigation of Racial and Ethnic Disparities in Service Utilization among Homeless Adults with Severe Mental Illness - Horvitz-Lennon, Marcela (2009)
OBJECTIVE: To determine if service disparities exist among severely mentally ill homeless adults, a vulnerable population with a high level of unmet need. METHODS: This study used data collected at baseline for 6,829 black, Latino, and non-Latino white participants in the Access to Community Care and Effective Services and Support study. Outcome variables were measures of utilization of psychiatric outpatient, housing, and case management services in the previous 60 days. The sample was divided into white/black and white/Latino cohorts. Within each cohort, participants were stratified into comparable groups using propensity scores that estimated log-odds of being black or Latino as a function of several confounding variables. White minus black/Latino differences in mean number of visits (a measure of intensity) and in the mean probability of at least 1 visit (a measure of access) were subsequently estimated. RESULTS: The study sample consisted of 50% black, 6% Latino, and 44% white participants. Service utilization was low for the three services regardless of race/ethnicity. On multivariate analyses of service utilization in the previous 60 days, blacks had fewer psychiatric outpatient visits than whites (mean difference [95% CI] = 0.46 [0.10, 0.81]) yet Latinos had more case management visits than whites (mean difference [95% CI] = −0.51 [−1.03, −0.05]). Access analyses did not reveal disparities. CONCLUSIONS: While blacks have lower intensity of psychiatric outpatient utilization than whites hence experiencing a service disparity, Latinos have higher intensity of case management utilization than whites. Possible contributors and clinical and methodological implications of these results are discussed.